2016
DOI: 10.1080/07391102.2015.1064832
|View full text |Cite
|
Sign up to set email alerts
|

A review on the salt bridge ASP177-ARG163 (O–N) of wild-type rabbit prion protein

Abstract: Abstract:Prion diseases are invariably fatal and highly infectious neurodegenerative diseases that affect a wide variety of mammalian species such as sheep and goats, cattle, deer, elks, humans and mice etc., but rabbits have a low susceptibility to be infected by prion diseases with respect to other species. The stability of rabbit prion protein is due to its highly ordered β2-α2 loop (PLoS One 5(10) e13273 X-ray file of the rabbit prion protein, we can clearly observe this salt bridge. This article analyses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The generation of transgenic rabbits expressing ovine PrP and their successful infection with scrapie prions definitively highlighted that the amino acid sequence of rabbit PrP C was responsible for the low susceptibility of rabbits to prion infections (14). Although rabbit PrP C has been studied in detail to identify distinctive structural elements that explain its low susceptibility to prion-like misfolding (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), the key elements or amino acid residues causing this behavior remain unknown.…”
mentioning
confidence: 99%
“…The generation of transgenic rabbits expressing ovine PrP and their successful infection with scrapie prions definitively highlighted that the amino acid sequence of rabbit PrP C was responsible for the low susceptibility of rabbits to prion infections (14). Although rabbit PrP C has been studied in detail to identify distinctive structural elements that explain its low susceptibility to prion-like misfolding (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), the key elements or amino acid residues causing this behavior remain unknown.…”
mentioning
confidence: 99%
“…An endeavor to systematically characterize the differences in the secondary structure and in the flexibility of the protein for a large number of PrP species through molecular dynamics simulations was attempted by Zhang (2018) . These studies identified a salt bridge between R164 and D178 ( Zhang and Wang, 2016 ) as important for the β2-α2 loop stability.…”
Section: Conformational Dynamics Of Prp Probed By Molecular Modelingmentioning
confidence: 99%
“…Studies focused on the CT3DD uncovered a key role for the solvent exposure of the highly conserved Y169 in stabilizing the 3 10 -turn ( Huang and Caflisch, 2015a , b ; Caldarulo et al, 2017 ). Lastly, the systematic characterization of the secondary structures and flexibility for many PrP species identified a critical salt bridge between R164 and D178 for the β2-α2 loop stability ( Zhang and Wang, 2016 ; Zhang, 2018 ).…”
Section: Introductionmentioning
confidence: 99%